Training on Microgreen Cultivation as a Strategy to Strengthen Food Security and Family Nutrition - Hifni Septina Carolina; Khodijah; Agus Setiawan; Suhono, Suhono (International Journal of Community Engagement Payungi, 2023)
The pandemic conditions since two years ago have left people vigilant about economic security, especially food security. Another problem is that the reduction of agricultural land and the density of residential housing has encouraged the emergence of a new concept of gardening on limited land. Agriculture in urban areas with minimal land is called Urban Farming by the agricultural community. This service aims to provide knowledge to partners about alternative strategies to strengthen family food security through microgreen cultivation. The method used in this service is the Community Based Research (CBR) approach, which prioritizes the utilization of assets and potentials that are around and owned by the community or society.  This activity was carried out in 3 stages; training, cultivation preparation and implementation of microgreen cultivation. Many people got the benefits and virtues of microgreen cultivation.  The partners of this service are community groups who are members of the WES (Women and Environmental Studies) Payungi community which focuses on women and environmental issues and actively participates in spreading knowledge about the environment to the surrounding community. By conducting this training to the partner group, the partners can practice growing microgreens for themselves and participate in introducing it to a wider community environment. Keywords: Strengthen Food Security, Food Security, Training on Microgreen Cultivation